Effects of perioperative clinical hypnosis on heart rate variability in patients undergoing oncologic surgery: secondary outcomes of a randomized controlled trial - Azam, Muhammad Abid; Weinrib, Aliza Z.; Slepian, P. Maxwell; Rosenbloom, Brittany N.; Waisman, Anna; Clarke, Hance; Katz, Joel (Frontiers in Pain Research, 2024)
Introduction Clinical hypnosis has been proposed for post-surgical pain management for its potential vagal-mediated anti-inflammatory properties. Evidence is needed to understand its effectiveness for post-surgical recovery. Iin this secondary outcome study, it was hypothesized that surgical oncology patients randomized to receive perioperative clinical hypnosis (CH) would demonstrate greater heart-rate variability (HRV) during rest and relaxation at a 1-month post-surgery assessment compared to a treatment-as-usual group (TAU). Methods After REB approval, trial registration and informed consent, 92 participants were randomized to receive CH (n = 45) or TAU (n = 47). CH participants received a CH session before surgery and during post-surgical in-hospital stay HRV was assessed during rest (5 min) and relaxation (10 min) before and 1-month after surgery. Pain intensity was obtained using a 0–10 numeric rating scale pre and post 1-week and 1-month post surgery. Results One month after surgery, HRV was significantly higher in CH group (n = 29) during rest and relaxation (both p < 0.05, d = 0.73) than TAU group (n = 28). By contrast, rest and relaxation HRV decreased from pre- to 1-month post-surgery for the TAU (both p < 0.001, d > 0.48) but not the CH group. Pain intensity increased from pre-surgery to 1-week post-surgery (p < 0.001, d = 0.50), and decreased from 1-week to 1-month post-surgery (p = 0.005, d = 0.21) for all participants. Discussion The results suggest that hypnosis prevents the deleterious effects of surgery on HRV by preserving pre-operative vagal activity. These findings underscore the potential of clinical hypnosis in mitigating the adverse effects of surgery on autonomic function and may have significant implications for enhancing post-surgical recovery and pain management strategies. Clinical Trial Registration ClinicalTrials.gov, identifier (NCT03730350).